Workload and Decision Errors in Copper Cathode Harvesting - Ira Galuh Ristanti; Tranggono Tranggono; Mega Cattleya Prameswari Anissa Islami (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Workload management is essential in high-risk manufacturing operations because excessive physical and cognitive demands can reduce concentration, productivity, and workplace safety. Specific Background: Copper cathode harvesting requires operators to work in demanding refinery conditions involving physical endurance, sustained attention, and accurate task execution. Knowledge Gap: Existing workload assessments often examine physical workload or human error separately, while integrated evidence combining cardiovascular load and cognitive reliability analysis in copper cathode harvesting remains limited. Aims: This study aimed to analyze operators’ physical and mental workload and identify potential human errors in copper cathode harvesting operations. Results: Using Cardiovascular Load and Cognitive Reliability and Error Analysis Method, data from 20 operators showed an average %CVL of 40.11%, classified as moderate physical workload, although one operator reached the heavy category and two operators reached the moderately heavy category. CREAM analysis placed the work in tactical control mode, with error probability ranging from 0.001 to 0.1. The highest Human Error Probability value was 0.1, found in evaluate, identify, and record cognitive activities. Novelty: This study integrates CVL and CREAM to connect physical workload, cognitive control mode, and human error probability in copper cathode harvesting. Implications: The findings support workload balancing, fatigue control, decision support, procedural reinforcement, and targeted safety improvements in refinery operations. Highlights: Average %CVL reached 40.11%, indicating a moderate burden category. Tactical control mode produced an error range of 0.001 to 0.1. Evaluate, identify, and record activities showed the highest HEP value. Keywords: CREAM, CVL, Human Error, Refinery Plant, Workload.